Sport w wychowaniu i ewangelizacji - Jerzy Kostorz (Nicolaus Copernicus University in Toruń, 2009)
Contemporary sport is one of the biggest cultural phenomenon of the 20th and 21st   century covering all the continents and nations. Huge amounts of money and milliards of   fans are involved in it. Sport is undeniably one of the most popular and most important   disciplines of human life. From the very beginning people have been improving the reality   they live in, also as far as sport is concerned. Thanks to the fact that nowadays media   are better and more accessible it has become a wide-spread occurrence. For contemporary   societies sports events are very significant. When it is based on humanistic foundations   and on the Olimpic ideals of ancient Greece, where sport was an integral part of education,   it can significantly influence the formation of a man's personality. Unfortunately,   degradation of sport through corruption, doping or disorderly behaviour of fans can also   be observed.   That is why it is crucial to constantly remind of the proper interpretation of sport   and its place in human's life and consequently its role in the process of education and   evangelization. At first, to present the topic of sport in the right way the phenomenon of it   is defined. Then sport is shown in the context of ethical and moral evaluation and its advantages   and disadvantages are presented. Afterwards, some possibilities of using sport in   the process of education are demonstrated. After that, sport is depicted as a contemporary   form of evangelization in the parish.